Francis of Assisi in the World of Cranach - Seubert, Xavier John (IKON, 2010)
Abstract The German Reformation is popularly romanticized as being set in motion by one Herculean figure, who dared to go face to face with the monolithic power and theology of the Roman Catholic Church. It is also thought that the Reformation was in essence iconoclastic, leaving in its wake churches totally cleansed of devotional statues and images. The reality, of course, is quite different. The pre- Reformation and Reformation periods were social, political and theological complexities, which we are still only learning to decipher. This paper will evaluate two images of St Francis of Assisi: one is a painting done in 1502 by Lucas Cranach the Elder and the other a woodcut done c. 1550. Not only is there a radical rupture in the use of images of the saint in these periods, but there is an even more radical continuity. The reversal of image and prototype, which takes place between Francis and Christ and which merits the condemnation of Luther, is the same reversal which eventually characterizes the images of Luther himself.